Vortex-induced vibrations of a circular cylinder with a pair of control rods of varying size - Jiménez-González, J.I.; Huera-Huarte, F.J. (Journal of sound and vibration, 2018)
We present an experimental study on the vortex-induced vibration (VIV) of a low mass-damping one-degree-of-freedom circular cylinder subject to uniform cross-flow, with pairs of control rods of varying size located in its wake. Two particular locations for control rods, selected according to recent experimental maps of VIV sensitivity to localized perturbations, have been tested for increasing control rod diameters, d. Important amplitude reductions are observed for all arrangements investigated, with nearly total suppression of oscillations (up to 90%) for control rods of d = 0.4D, where D is the diameter of the main cylinder. Force measurements have been used to describe the nature of changes observed in the wake and the mechanisms behind the VIV control. In general, the placement of control rod pairs in the near wake leads to an important weakening of the lift coefficient and alters substantially the phase between transverse force and cylinder displacement. Moreover, it is shown that, for some particular arrangements, attenuation of VIV is obtained along with a drag reduction of approximately 60% at the upper branch of amplitude response, rendering the present strategy an interesting and practical solution for VIV control when several cylinders need to be installed together.